The Role of the School Principal in Improving the Quality of Inclusive Education at SMP Negeri 6 South Halmahera, North Maluku Province - Marsumi; Romi J. Mongdong; Aldjon Nixon Dapa (JR Education, 2026)
Inclusive education has emerged as a pivotal policy mandate in Indonesia, requiring schools to accommodate all learners, including those with special needs, within regular educational settings; however, its quality implementation remains a formidable challenge, particularly in resource-constrained and geographically isolated areas. Effective school leadership is widely recognized as a key determinant of successful inclusive education, yet empirical evidence from junior secondary schools in remote island regions of Eastern Indonesia is critically lacking. This study aims to examine the role of the school principal in improving the quality of inclusive education at SMP Negeri 6 South Halmahera, North Maluku Province. A qualitative descriptive approach was employed, with data collected through semi-structured interviews, direct observations, and document analysis from purposively selected informants comprising the principal, teachers, and educational staff; data validity was ensured through source and technique triangulation. The findings reveal that the principal executes five interrelated roles, educator, manager, supervisor, motivator, and innovator, to build an inclusive school culture, with key strategies including socialization of inclusive education concepts, enhancement of teacher competencies, adaptation of learning methods and assessment systems, and the creation of a non-discriminatory school environment. Supporting factors include government policy support, strong commitment from the principal and teachers, and active parental participation, while inhibiting factors encompass limited facilities and infrastructure, a shortage of special education personnel, and insufficient training opportunities for regular classroom teachers. These findings affirm that participatory and adaptive school leadership is the central driver of inclusive education quality, even in severely resource-limited contexts, and that human leadership capital can effectively compensate for infrastructural deficits. This study implies that targeted leadership development programs and collaborative support networks for principals in remote Indonesian schools are urgently needed to sustain and scale inclusive education quality